Predator defense is shaped by risk, brood value and social group benefits in a cooperative breeder. (20th March 2020) - Teunissen, Niki; Kingma, Sjouke A; Peters, Anne
Abstract: Predation is a major cause of mortality and nest failure in birds. Cooperative predator defense can enhance nest success and adult survival but, because it is inherently risky, dynamic risk assessment theory predicts that individuals modify defense behavior according to the risk posed by the predator. Parental investment theory, on the other hand, predicts that reproductive payoffs (brood value) determine investment in nest defense. We propose that, in cooperative breeders, fitness benefits deriving from the survival of other group members may additionally influence defense behavior (social group benefits theory). We tested predictions of these theories in the cooperatively breeding purple-crowned fairy-wren, Malurus coronatus, where brood value is higher for breeders, but social group benefits more important for helpers. We recorded experimentally induced individual defense behaviors in response to predator models presented near nests, representing differing levels of threat to nests and adults. As predicted, 1) individuals engaged in less risky defenses when encountering a more dangerous predator (dynamic risk assessment theory); 2) individuals defended older broods more often, and breeders defended more than helpers (parental investment theory); and 3) helpers were more likely to respond to a predator of adults (social group benefits theory). Our findings highlight that predator defense in cooperative breeders is complex, shaped by the combination of immediate risk and multiple benefits. Abstract : Predator defense is important for reproduction and survival. We show that, in a cooperative breeder, predator defense is complex and shaped by risk and multiple benefits. Individuals take fewer risks with more dangerous predators, and defense by breeders and helpers is shaped by different benefits. Breeders benefit more from brood survival and defend more against nest predators, whereas helpers receive important benefits from social group members and defend more against predators of adults in particular.